KARAKTERISASI MORFOLOGIS DAN KAJIAN FENOLOGI DAUN TAPAK DARA (Catharanthus roseus (L.) G. DON) - Ilahi, Muhammad Fazli; Murni, Pinta; Sanjaya, M. Erick (Universitas Jambi, 2026)
Indonesia has high biodiversity, including flora with ecological, economic, and health values, one of which is periwinkle (Catharanthus roseus (L.) G. Don) which is used as an ornamental and medicinal plant. However, studies on the phenology and morphological characterization of periwinkle leaves are still limited, so this study aims to analyze the morphological and phenological characterization of its leaves. The study was conducted for 66 days with an observational descriptive method using qualitative and quantitative approaches. The research sample for morphological and phenological characterization of leaves consisted of 15 leaves from 5 stems of the same plant. Characterization was carried out when the leaves were fully expanded. The samples observed were in the gardens of residents' homes in Mendalo Indah, Jambi Luar Kota District, Muaro Jambi, Jambi Province. Observations were carried out every day at 11:00 – 13:00 WIB starting from the emergence of leaf shoots until the leaves fall. Environmental factors were measured using the Galaxy Sensor and AccuWeather applications. The results of the study showed that the periwinkle (C. roseus (L.) G. Don) leaves are classified as single leaves with an oblong shape, blunt tips and bases, and pinnate leaf bone arrangement, flat leaf edges, and their location is oppositely crossed, where every two leaves on the stem node are arranged crosswise with the two leaves below. The phenology includes the initiation phase to morphogenesis for 3 days, leaf bud opening for 3 days, expansion phase for 14 days, yellowing leaf phase for 31 days, and leaf fall 15 days after. Environmental conditions during the observation were temperature 23.9 – 41.7 °C, air humidity 31.2 – 51.2%, light intensity 136.38 – 25781.00 Lux, and rainfall 0 – 34 mm.